Investigating the criminals exposed to inter-partner violence and child abuse: A case-control study - Sonia Oveisi; Malihe Mahboobi; Hui Chen (Wolters Kluwer Medknow Publications, 2020)
Introduction: There are numerous studies on the intergenerational transmission of violence and criminal acts. However, the role of the confounding factors has been suggested as social and contextual factors. This study investigated whether violent criminals are more exposed to both their parents' inter-partner violence (IPV) and their own childhood abuse in comparison to noncriminal people after controlling for potentially confounding factors. Methods: This is a retrospective study on 101 Iranian young medical students at the Qazvin University of Medical Science (control) and 98 young adults who have been imprisoned in Choobindar prison due to violent crimes. Two groups have been assessed by Adult Recall Version of The Revised Conflict Tactics Scales: CTS2-CA and CTSPC-CA questionnaires. Results: Logistic regression of IPV and demographic variables showed that exp(β) for father's and mother's education in criminals is 0.307 and 0.203, respectively. Father's and mother's education were significant predictors of inter-partner violence among criminals with odds ratio of 0.24 and 0.29, respectively. Furthermore, childhood psychological aggregation and neglect are meaningful factors. Conclusion: After controlling for potentially confounding risk factors, multinomial logistic regression analyses revealed that a history of witness IPV is not associated with the criminal act. The family context is important which they grew up in, such as mother's and father's education. Many criminal acts are the result of a combination of several factors, such as psychological, educational, cultural, social, and economic factors.